2009
DOI: 10.1093/eurheartj/ehp552
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury following transcatheter aortic valve implantation: predictive factors, prognostic value, and comparison with surgical aortic valve replacement

Abstract: AimsVery few data exist on the occurrence of acute kidney injury (AKI) associated with transcatheter aortic valve implantation (TAVI). The objectives of the present study were (i) to determine the incidence, predictive factors, and prognostic value of AKI following TAVI, and (ii) to compare the occurrence of AKI in TAVI vs. surgical aortic valve replacement (SAVR) in patients with pre-procedural chronic kidney disease (CKD).Methods and resultsA total of 213 patients (mean age 82 ± 8 years) undergoing TAVI for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
288
10
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(369 citation statements)
references
References 24 publications
(32 reference statements)
55
288
10
6
Order By: Relevance
“…Many studies examining the predictors of death in AKI are restricted to patients who received acute dialysis (3)(4)(5)(6)(7)(8)(9), limiting generalizable inferences regarding the broader AKI population. Other studies have enrolled patients after consultation with a nephrologist (10), restricted to intensive care unit (ICU) settings (2), or after surgical procedures (11)(12)(13)(14). Some observational studies lack the patient-level data needed to adequately adjust for comorbid illness, and utilize limited registry data to categorize AKI (15).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies examining the predictors of death in AKI are restricted to patients who received acute dialysis (3)(4)(5)(6)(7)(8)(9), limiting generalizable inferences regarding the broader AKI population. Other studies have enrolled patients after consultation with a nephrologist (10), restricted to intensive care unit (ICU) settings (2), or after surgical procedures (11)(12)(13)(14). Some observational studies lack the patient-level data needed to adequately adjust for comorbid illness, and utilize limited registry data to categorize AKI (15).…”
Section: Introductionmentioning
confidence: 99%
“…We have successively simplified our procedure protocol with the result that some complications associated with the procedure have been reduced or totally avoided. Elderly patients with impaired kidney function are more at risk for acute renal failure and are sensitive to contrast medium, though some controversy exists about the negative effect of contrast delivery in association with TAVI [14,15]. In a large multicenter study, Barbanti et al [7] reported that acute kidney injury is a frequent complication and has significant impact on both early and long-term TAVI survival [7].…”
Section: Discussionmentioning
confidence: 99%
“…A limited clinical experiment suggests that the renal function often improves with the best cardiac output after AE correction. ARF is usually mild and easily reversed and less common than in surgical patients 33 . Coronary obstruction rarely occurs and is a result of the native valve displacement of the left coronary ostium.…”
Section: Discussionmentioning
confidence: 99%